Experimental and Theoretical Evaluation of Incident Solar Irradiance on Photovoltaic Power Plants Under Real Operating Conditions: Fixed Tilt Angle System vs. Horizontal Single-Axis Tracker - Arsenio Barbón; Jaime Martínez-Suárez; Luis Bayón; José A. Fernández-Rubiera (Applied Sciences)
The aim of this paper was to delve deeper into the nuances of incident solar irradiance on the photovoltaic field of a fixed tilt angle system versus a horizontal single-axis tracker. The fixed tilt angle system was used as a baseline for comparison. Three assessment indicators were analysed (annual energy gain (<semantics>AEG</semantics>), monthly energy gain (<semantics>MEG</semantics>), daily energy gain (<semantics>DEG</semantics>)). The procedure used comprised the following steps: (i) choice of solar irradiance estimation model; (ii) theoretical study; (iii) study under real operating conditions—for this purpose, an experimental setup was used; and (iv) comparison of these studies. The experimental setup was installed at the Department of Electrical Engineering of the University of Oviedo (Gijón, Spain) (latitude <semantics>43°31′22″</semantics> N, longitude <semantics>05°43′07″</semantics> W, elevation 28 (m) above sea level). Gijón is characterised by a temperate oceanic climate typical of Spain’s Atlantic coast, with cool summers and wet and mostly mild winters. The code assigned to Gijón under the Köppen climate classification is <semantics>Cfb</semantics>. The horizontal single-axis trackers that comprise photovoltaic power plants have three operating modes (Scenario 1). Some studies consider a unique mode of operation from sunrise to sunset (Scenario 2). The following conclusions can be drawn from the results obtained: (i) although the results obtained in the theoretical study and in the study under real operating conditions were different, a trend can be seen in the results; for example, the <semantics>AEG</semantics> obtained was approximately <semantics>13%</semantics> and <semantics>8.5%</semantics> in the theoretical study and in the real study, respectively, in Scenario 1 and approximately <semantics>18%</semantics> and <semantics>10.5%</semantics>, respectively, in Scenario 2; Scenario 2 obtained higher results than Scenario 1 in all the assessment indicators; but it must be considered that Scenario 1 is the real mode of operation; (ii) from March to September, the horizontal single-axis tracker generates more electrical energy; as this period contains the months of greatest solar irradiance, the horizontal single-axis tracker performs better annually; considering the theoretical study and Scenario 1, the highest value of <semantics>MEG</semantics> was in June (<semantics>43%</semantics>) and the lowest was in December (<semantics>−29%</semantics>); when the study was considered under real operating conditions, the highest result was in July (<semantics>30%</semantics>) and the lowest was in December (<semantics>−24%</semantics>); (iii) on the days between 70 and 277 in Scenario 1, the horizontal single-axis tracker generated more electrical energy; on the other days the opposite occurred; taking into account the theoretical study, the highest and lowest <semantics>DEG</semantics> values were <semantics>43%</semantics> and <semantics>−30%</semantics>, respectively; when the study was considered under real operating conditions, the highest and lowest <semantics>DEG</semantics> values were <semantics>58%</semantics> and <semantics>−47%</semantics>, respectively.